A new species of Ranthidiellum from Thailand, with a key to the species (Hymenoptera: Megachilidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2009)
A new species of anthidiine bee (Megachilidae: Megachilinae: Anthidiini), Anthidiellum (Ranthidiellum) ignotum sp. n., is described and figured from northeastern Thailand, the furthest North this subgenus has yet been recorded.The species is distinguished from its congeners, being most similar to A. (R.) apicepilosum (Dover) in the coloration of the legs, but is otherwise quite unique for the group. A provisional key to the species of Ranthidiellum is provided.
Keywords: čebele; entomologija; nove vrste; Tajska; taksonomija; zoogeografija